Endangered species - Benson, Sonia; Nagel, Rob. (Farmington Hills, MI : UXL, 2004)
Entries on more than 200 extinct, endangered, vulnerable, and threatened animals and plants describe the individual species, its habitat and current distribution, and efforts to protect and preserve it
vol 1. Mammals -- vol. 2. Arachnids, birds, crustaceans, insects, and mollusks -- vol. 3. Amphibians, fish, plants, and reptiles
Rev. ed. of: Endangered species / Rob Nagel. c1999
Includes bibliographical references (xli-l) and index
Keywords: Endangered species -- Juvenile literature; Endangered species -- Encyclopedias